MGM-DVD Hollywood classics reviewed - McDonagh, Maitland (Dance Books Ltd., Alton,Hampshire (UK), 2001)
Review of Hollywood classics. PALABRAS CLAVE: dance movies, MGM musicals, Broadway, Singin' in the Rain, Seven Brides for the Seven Brothers, Royal Wedding.
Warner Home Videos: Singin' in the Rain. Seven Brides for the Seven Brothers. Royal Wedding Sanctuary.